Genetic parameters of andrological traits in bovine - Silva, M. R. [UNESP]; Pedrosa, V. B.; Silva, J. B. C. [UNESP]; Herrera, L. G. G.; Eler, J. P.; Albuquerque, Lucia Galvão de [UNESP] (Univ Austral Chile, Fac Ciencias Veterinarias, 2012)
The sexual precocity and fertility of bovines have great impact on the economic success of commercial cattle herds, where some reproductive traits have been adopted as selection criteria. However, the majority of these traits depend on reproductive events of the females and, with exception of the scrotal circumference, few studies approach others andrological traits. The estimation of heritabilities and genetic correlations of testicular and seminal traits and also sexual behaviour, will allow to provide alternatives for the design of more appropriate selection strategies for fertility, together with other economic traits.
Keywords: Cattle; Genetic correlation; Breeding soundness; Heritability